2015
DOI: 10.3906/sag-1403-113
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of diffusion-weighted magnetic resonance imaging in the evaluation of extrahepatic cholestasis-related hepatic fibrosis

Abstract: Background/aim: To investigate the efficacy of diffusion-weighted magnetic resonance imaging (DWI) in the diagnosis and staging of fibrosis induced by experimental bile duct ligation (BDL).Materials and methods: Twenty-four rats were divided randomly into four groups: control, BDL -3 days, BDL -2 weeks, and BDL -4 weeks. DWI was performed with b-values of 100 and 500 on the rats from control group at day zero, on the rats from the BDL -3 days group at the end of day 3, on the rats from the BDL -2 weeks group a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…Liver fibrosis by increasing barriers and associated reduction in vascularity leads to reduced ADC values. Studies have demonstrated that DWI is an accurate technique for detection of fibrosis11,12 while other studies have shown poor performance of DWI 13,14. However, there is no established standard technique for performing DWI for staging liver fibrosis and optimal b-values remain unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Liver fibrosis by increasing barriers and associated reduction in vascularity leads to reduced ADC values. Studies have demonstrated that DWI is an accurate technique for detection of fibrosis11,12 while other studies have shown poor performance of DWI 13,14. However, there is no established standard technique for performing DWI for staging liver fibrosis and optimal b-values remain unknown.…”
Section: Introductionmentioning
confidence: 99%